2009
DOI: 10.3201/eid1509.081228
|View full text |Cite
|
Sign up to set email alerts
|

Trends in US Hospital Admissions for Skin and Soft Tissue Infections

Abstract: Using data from the 2000–2004 US Healthcare Cost and Utilization Project National Inpatient Sample, we found that total hospital admissions for skin and soft tissue infections increased by 29% during 2000–2004; admissions for pneumonia were largely unchanged. These results are consistent with recent reported increases in community-associated methicillin-resistant Staphylococcus aureus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
206
1
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(221 citation statements)
references
References 7 publications
5
206
1
9
Order By: Relevance
“…[4][5][6] It is also a leading cause of keratitis, a community acquired infection that occurs mainly in contact lens wearers and those with corneal injury. 7,8 Hospital and community isolates both are increasingly methicillin resistant and resistant to third generation fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It is also a leading cause of keratitis, a community acquired infection that occurs mainly in contact lens wearers and those with corneal injury. 7,8 Hospital and community isolates both are increasingly methicillin resistant and resistant to third generation fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from the Healthcare Cost and Utilization Project National Inpatient sample, Edelsberg et al 3 found a 29% increase in hospital admissions for SSTIs during a 5-year period (2000)(2001)(2002)(2003)(2004). In a study that assessed the incremental clinical and economic burden of hospitalized patients with a secondary diagnosis of SSTIs compared with matched controls without SSTIs, patients with SSTIs had a mean of 3.8 additional days of hospitalization, $14,794 excess hospital charges, and an increased risk of mortality (odds ratio, 1.32).…”
mentioning
confidence: 99%
“…6 Current trends indicate the expanding reservoir of MRSA in the community is likely to become a source for recurrent transmission into hospitals where it would put many more patients at risk for developing highly virulent and multidrug resistant infections. 7 Due to the steady decrease in the rate of new antibiotics reaching the market, an urgent need exists for the development of alternate therapeutic approaches.…”
mentioning
confidence: 99%